Structured Analysis of a Generator Set Lubrication System Using Vertex Articulation in Plithogenic n-SuperHyperGraphs - Gonzalo X. Vizuete; Cristian F. Gallardo; Gabriela Vizuete (Neutrosophic Sets and Systems)
The primary function of the generator set installed in a remote oil field location is to supply electrical power for crude oil extraction. Due to operational demands, the lubrication system was upgraded to improve oil quality and reduce particulate contamination. This study assessed particulate contamination by applying the ISO 4406 cleanliness code, evaluating oil properties, and monitoring engine wear, using the Plithogenic n-SuperHyperGraph model as a structural framework. Oil samples were analyzed before and after implementing an external microfiltration system. Initial ISO codes of 22/21/19 were recorded; after 552 hours of operation, the ISO code improved to 19/18/15, achieving 91.25% efficiency. Post-1051-hour analyses confirmed wear levels remained below the control limit. The results demonstrate the system’s technical and operational viability, supporting its potential economic and environmental feasibility in similar industrial settings.